Associations Between Self, Peer, and Teacher Reports of Victimization and Social Skills in School in Children With Language Disorders - Sureda-Garcia, Inmaculada; Valera-Pozo, Mario; Sanchez-Azanza, Victor; Adrover-Roig, Daniel; Aguilar-Mediavilla, Eva (Frontiers in Psychology, 2021)
Previous studies have shown that teachers and parents of children with language disorders report them to have higher victimization scores, a heightened risk of low-quality friendships and social difficulties, and may be more vulnerable to peer rejection than control peers. However, there are few studies of bullying in children with developmental language disorder (DLD) and reading difficulties (RD), and none has considered the mutual relationships between teacher reports, the perceptions of classmates, and children’s self-reports. We analyzed the experiences of bullying and peer relationships in primary school students with DLD and RD as compared to their age-matched peers using teacher reports, peer reports, and self-reports on victimization. Additionally, we explored how associated are these three perspectives. Results indicated lower levels of peer-rated prosocial skills in DLD and RD students compared to their peers, as well as higher levels of victimization as assessed by peers for students with DLD. In the same line, the teachers' ratings showed that students with DLD presented poorer social skills, less adaptability, and more withdrawal in social interaction. Contrastingly, self-reports informed of similar rates of interpersonal relationships, social stress, and peer victimization between the three groups. Consequently, we found significant correlations between measures of peer reports and teacher reports that contrasted with the lack of correlations between self and other agents’ reports. These findings stress the importance of using self-reports, peer reports, and teacher reports at the same time to detect bullying situations that might go unnoticed.